Sulfonic acid modified hollow polymer nanospheres with tunable wall-thickness for improving biodiesel synthesis efficiency. Issue 11 (15th May 2020) - Song, Wenliang; Zhang, Yu; Varyambath, Anuraj; Kim, Ji Su; Kim, Il
Abstract : A green and efficient method has been developed to fabricate sulfonic acid-functionalized hollow acidic spherical catalysts with tunable shell thicknesses. Abstract : Precisely designing the morphology and size of nanostructures is vital in green chemistry as various advanced applications depend upon the shapes and dimensions of the functionalised materials. Herein, we report on a green and efficient self-assembly strategy for synthesising hollow polymeric nanospheres with tunable wall thicknesses. The morphology and shell thickness of the nanospheres can be easily tailored by rationally manipulating monomer and catalyst combinations during the one-pot Friedel–Crafts polymerisation process, without using any templates or surfactants. Heterogeneous solid sulfonic acid catalysts can be easily achieved via the post-sulfonation strategy. These porous materials have preferable surface areas, ordered hollow pore structures, and accessible acidic sites, and they serve as promising catalysts for biodiesel production. This study provides insights into the production of template- and metal-free based catalysts for biofuel production, which is imperative for the green and efficient design and manufacture of high-activity heterogeneous catalysts.